Natality and calf mortality of the Northern Alaska Peninsula and Southern Alaska Peninsula caribou herds - Sellers, Richard A.; Valkenburg, Patrick; Squibb, Ronald C.; Dale, Bruce W.; Zarnke, Randall L. (Rangifer, 2003)
We studied natality in the Northern Alaska Peninsula (NAP) and Southern Alaska Peninsula (SAP) caribou (Rangifer tarandus granti) herds during 1996-1999, and mortality and weights of calves during 1998 and 1999- Natality was lower in the NAP than the SAP primarily because most 3-year-old females did not produce calves in the NAP Patterns of calf mortality in the NAP and SAP differed from those in Interior Alaska primarily because neonatal (i.e., during the first 2 weeks of life) mortality was relatively low, but mortality continued to be significant through August in both herds, and aggregate annual mortality was extreme (86%) in the NAP Predators probably killed more neonatal calves in the SAP, primarily because a wolf den (Canis lupus) was located on the calving area. Despite the relatively high density of brown bears (Ursus arctos) and bald eagles (Haliaeetus leucocephalus), these predators killed surprisingly few calves. Golden eagles (Aquila chrysaetos) were uncommon on the Alaska Peninsula. At least 2 calves apparently died from pneu¬monia in the range of the NAP but none were suspected to have died from disease in the range of the SAP. Heavy scav¬enging by bald eagles complicated determining cause of death of calves in both the NAP and SAP.